Neighbours around the world : an international look at the people next door - Cheshire, Lynda (Emerald Publishing Limited, 2022)
Neighbours are a lively topic of everyday conversation and interest. Neighbours Around the World takes a comparative look around the world at our relationships and interactions with the people who live next door, analysing the ways in which these relationships are changing in the face of large-scale macro social and urban processes. Understanding that there is considerable variation in the relative importance that we place on neighbours - the extent to which we interact with them or rely on them for local support, and the likelihood that our relationships with them are characterised by friendliness, indifference or conflict - this edited collection examines how neighbouring is shaped by our individual characteristics, but also by the structural features of where we live and the forces reshaping our local neighbourhoods. Casting a conceptual and empirical gaze on neighbours as a constituent feature of urban life in diverse cities, neighbourhoods and local streets around the world, the authors take us from Singapore's public housing estates to mobile home parks in Florida, and from one of the most famous tourist spots in Shanghai to new-build estates on the edge of Moscow and St Petersburg. Neighbours Around the World uncovers the diversity and commonalities in the meanings, experiences and practices of living with neighbours--the people next door.